A novel approach of integrated bioprocessing of cane molasses for production of prebiotic and functional bioproducts. (November 2016) - Sharma, Manisha; Patel, Satya Narayan; Lata, Kusum; Singh, Umesh; Krishania, Meena; Sangwan, Rajender S.; Singh, Sudhir P.
Highlights: Cane molasses was demonstrated as a low-cost feedstock for enzymatic production of prebiotic oligosaccharides. The oligosaccharides showed resistance to enzymatic hydrolysis. Freed -fructose generated as by-product during acceptor reactions in cane molasses was transformed intod -psicose. Cane molasses was established as a replacer of synthetic culture medium for dextransucrase enzyme production. Abstract: In this work, the sugar industry by-product cane molasses was investigated as feedstock for acceptor reactions by dextransucrase from Leuconostoc mesenteroides MTCC 10508, leading to the biosynthesis of oligosaccharides. The starch industry corn fiber residue was used as a source for acceptor molecules, maltose, in the reaction. Production of approximately 124 g oligosaccharides (DP3-DP6) per kg of fresh molasses was achieved. Further, cane molasses based medium was demonstrated as a sole carbon source for L. mesenteroides growth and dextransucrase production.d -Fructose released by dextransucrase activity as processing by-product was transformed into the functional monosaccharide with zero caloric value, d -psicose, by inducing its epimerization. Quantitative analysis approximated 37 gd -psicose per kg of fresh molasses. Thus, the study established a novel approach of integrated bioprocessing of cane molasses into prebiotic and functional food additives.